2012
DOI: 10.1681/asn.2011111130
|View full text |Cite
|
Sign up to set email alerts
|

IL-2/IL-2Ab Complexes Induce Regulatory T Cell Expansion and Protect against Proteinuric CKD

Abstract: Regulatory T cells (Tregs) help protect against autoimmune renal injury. The use of agonist antibodies and antibody/cytokine combinations to expand Tregs in vivo may have therapeutic potential for renal disease. Here, we investigated the effects of administering IL-2/IL-2Ab complexes in mice with adriamycin nephropathy, a model of proteinuric kidney disease that resembles human focal segmental glomerulosclerosis. Injecting IL-2/IL-2Ab complexes before or, to a lesser extent, after induction of disease promoted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 21 publications
2
60
0
Order By: Relevance
“…Inflammation is an important component of the pathophysiology of ADR nephropathy (7,22,26,33). Histological assessment of the kidneys of ADR-treated mice shows tubulointerstitial inflammation with infiltration of T and B lymphocytes and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is an important component of the pathophysiology of ADR nephropathy (7,22,26,33). Histological assessment of the kidneys of ADR-treated mice shows tubulointerstitial inflammation with infiltration of T and B lymphocytes and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…These data would rather argue against IL-2R crosslinking by IL-2/ S4B6 complexes. For IL-2/JES6-1 complexes, STAT5 phosphorylation was reduced in CD25 + YT-1 human NK cells compared with IL-2 in vitro [13], although another report using in vitro stimulation of total mouse splenocytes suggested that, compared with IL-2, IL-2/JES6-1 complexes led to increased STAT5 phosphorylation in CD4 + T cells [71]. In line with the former Recent structural data not only provide evidence for the steric aspects of the abovementioned model but also suggest mild antagonistic and allosteric forces at work (Figure 3).…”
Section: Il-2/mab Complexesmentioning
confidence: 98%
“…Furthermore, the IL-2C treatment showed its therapeutic potential in adriamycin nephropathy, a form of CKD. 11 However, there has been no study for the effect of the IL-2C on AKI. Here, we investigated whether the IL-2C can attenuate renal IRI by inducing Tregs using murine models.…”
mentioning
confidence: 99%